Divergent effects of 3-nitrooxypropanol on enteric methane emissions in Holstein and Brown Swiss cows, and its lack of synergy with acacia tannin extract - M.Z. Islam; S.E. Räisänen; T. He; C. Kunz; Y. Li; X. Ma; A.M. Serviento; K. Wang; M. Wang; Z. Zeng; M. Niu (Animal)
Enteric methane (CH4), the major contributor to on-farm greenhouse gas emissions, is a key mitigation target due to its high short-term global warming potential. The objectives of this study were to investigate the combined effects of 3-nitrooxypropanol (3-NOP) and Acacia mearnsii tannin extract (TAN), and their interactions with dairy cattle breed [Brown Swiss (BS) vs Holstein Friesian (HF)] on lactational performance and CH4 emissions. Sixteen multiparous mid-lactation cows, including 8 BS and 8 HF cows, were used in a split-plot design, with breed as the main plot. Cows within each subplot were arranged in a replicated 4 × 4 Latin Square design with a 2 × 2 factorial arrangement of treatments across four 24-d periods, including 3-d of sampling. The experimental diets were: (1) CON (basal total mixed ration), (2) 3-NOP (60 mg/kg DM), (3) TAN (3% of DM), and (4) 3-NOP + TAN. Spot samples of urine, faeces, and gas emissions (via GreenFeed) were collected at the end of each period 8 times over 3 days. No 3-NOP × TAN × Breed interactions were observed for DM intake (DMI), milk production, or enteric gas emissions, except for CH4 yield (g/kg DMI) and CO2 production. Breed influenced DMI, milk production, and component yields, with HF cows consuming 3.7 kg/d more DMI, producing 9.3 kg/d more milk, and achieving greater feed efficiency and higher milk component yields than BS cows. Milk yield and energy-corrected milk (ECM) tended to increase in HF but tended to decrease in BS cows by 3-NOP. Cows fed TAN had 1 kg/d lower DMI with the tendency for 3-NOP × TAN that showed greater reduction when TAN was fed alone, but milk yield, ECM, and feed efficiency remained unchanged. Cows fed TAN exhibited 18% lower milk urea nitrogen (N) concentration and 23.0% lower urinary N but 36.7% greater faecal N excretions as a percentage of daily N intake. A 3-NOP × Breed interaction was observed in CH4 production (g/d), with a 21.7% reduction in HF, and a 13.0% reduction in BS. Similarly, there were 3-NOP × Breed tendencies in CH4 yield and intensity (g/kg ECM), with reductions in HF cows of 21.8 and 23.4%, respectively, compared to 11.0 and 10.8% in BS cows. In conclusion, there were no synergistic or additive effects between 3-NOP and TAN on enteric CH4 mitigation. The enteric CH4 emission mitigating effect of 3-NOP was more pronounced in HF cows than in BS cows. Further research is needed to understand breed-specific responses and to optimise CH4 mitigation strategies for inclusion in national greenhouse gas inventories.